Analisa Kecelakaan Kerja Menggunakan Metode Fuzzy FMEA pada Proses Produksi UD Selebriti Gresik - Dias Mahardhika; Dian Palupi Restuputri; Shanty Kusuma Dewi (Journal of Industrial View, 2023)
Occupational safety is something that needs to be considered in a production process because it can affect worker performance. This is related to increased costs and decreased health conditions of workers. Work accidents are caused by a bad working atmosphere, inadequate training, low employee awareness, or lack of attention. In this study an analysis of work accidents at UD. Celebrities use the Fuzzy FMEA method. Based on the calculation results, there are 2 work accidents with the highest FRPN value.